2014
DOI: 10.3109/02713683.2014.902073
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Analysis of Quiescent and Activated Keratocytes: A Review ofEx VivoandIn VivoFindings

Abstract: Keratocytes are specialized, neural crest-derived mesenchymal cells occupying approximately 3% of the corneal stromal volume. They reside between the collagen lamellae and are responsible for the secretion of extracellular matrix macromolecules, thus contributing to the corneal transparency and integrity. During the regeneration process after infection, traumata and refractive surgery, the keratocytes undergo transition into divergent phenotypes, which are referred to as "activated keratocytes". Quite shortly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 66 publications
0
28
0
1
Order By: Relevance
“…As quiescent keratocytes remain dormant in their native state, activated keratocytes appear to reflect the level of intrastromal inflammation in response to cytokines and other inflammatory mediators, including interleukin (IL)-1 and tumor necrosis factor (TNF)-α [13,14,23,25]. Moreover, Beauregard et al [17] reported that an inflammation-independent alloimmune response caused by delayed-type hypersensitivity reactions leads to apoptosis of keratocytes in the stroma and contributes to graft failure [12].…”
Section: In Vivo Confocal Microscopy Evaluation Of Immune Cells In Thmentioning
confidence: 99%
“…As quiescent keratocytes remain dormant in their native state, activated keratocytes appear to reflect the level of intrastromal inflammation in response to cytokines and other inflammatory mediators, including interleukin (IL)-1 and tumor necrosis factor (TNF)-α [13,14,23,25]. Moreover, Beauregard et al [17] reported that an inflammation-independent alloimmune response caused by delayed-type hypersensitivity reactions leads to apoptosis of keratocytes in the stroma and contributes to graft failure [12].…”
Section: In Vivo Confocal Microscopy Evaluation Of Immune Cells In Thmentioning
confidence: 99%
“…After differentiation, hTMSCs tended to become more energetic state by using oxidative phosphorylation to produce ATP by mitochondrial respiration rather than by glycolysis; this change increased the extracellular acidification rate. Keratocytes are typical elongated and spindle-shaped [42]. The hTMSCs showed this morphology after KDM treatment; this observation suggests that hTMSCs were well-differentiated to keratocytes.…”
Section: Discussionmentioning
confidence: 71%
“…12.9. There is evidence that these morphological changes appear in the process of cell death when apoptotic vesicles in the keratocyte stroma turn transparent cellular part into accumulation of highly scattering elements [34]. These ghost cells finally disappear totally and after days are replaced by spindle shaped migrating keratocyte subtypes migrating from adjacent corneal areas.…”
Section: Corneal Keratocyte: a Neglected Entity Of Cellsmentioning
confidence: 99%
“…Furthermore, a number of studies deal with mice models to investigate diabetes-induced small fiber neuropathy [46,47]. Hovakimyan et al have investigated matrix-based regenerating agent for corneal wound healing after collagen cross-linking [34].…”
Section: Cslm For Animal Studiesmentioning
confidence: 99%